Penerapan City Branding Sebagai Promosi Eduwisata Kebun Kelor di Kelurahan Pulorejo Kota Mojokerto - Shabdayagra Gilang Rahmadhani; Rakhmat Saiful Ramadhani; Ratnaningrum Z.D (Institut Nalanda, 2024)
This study aims to identify and analyze the branding strategies implemented by Pokdarwis (Tourism Awareness Group) and KWT (Women Farmers Group) in promoting the Eduwisata Kebun Kelor in Pulorejo, Mojokerto City. The branding of Eduwisata Kebun Kelor is carried out through print media such as brochures that offer various educational tour packages, which teach tourists about moringa leaves and the process of making moringa-based products. The method used in this research is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results show that promotion is carried out through various means such as word of mouth, print media in the form of brochures, promotion through social media, although not yet fully optimal, and promotion from various local media covering Eduwisata Kebun Kelor. All these efforts have increased the visibility of Kebun Kelor. This study provides insights into the importance of branding strategies and community cooperation in promoting Eduwisata Kebun Kelor.